The Effect of Aspergilius Niger Fungus on the Development of Fungus Defect in Matured Raw Meat - Dashtoyan, A. L.; Nazaryan, S. Z. (ՀԱԱՀ հիմնադրամ)
Meat is a source of complete proteins of animal origin, which is necessary for the construction of human body tissues, synthesis and exchange of substances. In the RA, serious attention is paid to obtaining meat raw materials, sanitary and hygienic requirements and storage. However, even a high level of control does not allow consumers to be protected from the presence of low-quality and defective meat raw materials at consumption points. Sometimes they occur in meat raw materials of non-slaughterhouse origin, sometimes as a result of violating the rules of storage and transportation. The purpose of the work is to select and separate defective beef raw materials and to find out the defect causes.
Keywords: Food Science and Technology